A resilient hierarchical distributed model of a cyber physical system. Issue 2 (3rd April 2023) - Yadav, Surya B
ABSTRACT: We present a novel modelling scheme to develop a resilient hierarchical distributed model of industrial cyber-physical systems amenable to feedback control. It advances the current research work on cyber-physical system security and resilience by integrating security and self-adaptation features into each of the self-contained units (subsystems) of a cyber-physical system. We compare the proposed modelling scheme with the extant schemes. The proposed scheme is more comprehensive than the extant research work on resilient modelling scheme. The modelling scheme can be used to design resilient cyber-physical systems and build models to assess their security and resilience.